Two factor authentication by using SMS for web based application - Hamid Ali, Firkhan Ali; Mohammad Hanza, Mohammad Zaim; Mohd Sukri, Mohd Khairul Amin (WARSE, 2020)
Two factor authentications had two entry levels for authentication’s mechanism. This study had used Short Messaging Service (SMS) technology as a second factor in doing authentication on the web application. It can minimize the problems that occur regarding to the illegal access over the user privacy information on the Internet. The system that uses two factor authentications is capable to give the priority and safety in aspect of user’s privacy information from the web based applications.